AHMAD BIN HANBAL (PEMIKIRAN FIKIH DAN USHUL FIKIHNYA) - Marzuki, Marzuki (Institut Agama Islam Negeri (IAIN) Palu, 2005)
Ahmad bin Hanbal is popular not only as a faqih but also as a muhaddith. His authority on istimbath can be seen from his method of istimbath. He places the Qurâan and hadith as the main sources of law in his istimbath. In addition, he employs companionsâ fatwa agreed upon by them. The reason for this is that companions are undoubtedly credible persons. Other sources of law he uses in his istimbath are hadith mursal and hadith dhaâif, that is hadith of no tsiqah in some of its narrators. He alsoÂ employs such methods of istimbath as qiyas, ijmaâ, al-mashalih al-mursalah, istihsan, sad al-zariâah, andÂ istihsab.Kata kunci :Â Ahmad bin Hanbal, fikih, ushul fikih